Perancangan Desain Pengembangan Industri Makanan Tradisonal Minangkabau yang Berdaya Saing Global - Eka Rosalina; Afridian Wirahadi Ahmad (Akuntansi dan Manajemen, 2017)
This study aims to discuss the design strategy of traditional minangkabau food development in West Sumatra Province and to provide policy recommendation for traditional minangkabau food to be globally competitive. Tourism in the Minangkabau region is known in three things: culinary tourism (traditional food), nature tourism and cultural tourism. Ideally, whatever the destination in West Sumatra, each region always highlight the uniqueness of traditional food, but it is difficult to find traditional minangkabau food, especially in tourist areas. Culinary business that grow precisely fast food. The study was conducted on all regencies / cities in West Sumatra. Data collection techniques through interviews and questionnaires and FGDs. The data analysis was performed by IFAS analysis tool, EFAS.